Role of anaerobes in polymicrobial communities and biofilms complicating diabetic foot ulcers. Issue 5 (4th June 2018) - Percival, Steven L; Malone, Matthew; Mayer, Dieter; Salisbury, Anne‐Marie; Schultz, Gregory
Abstract : Infected tissues in the feet of people with diabetes in the form of a diabetic foot ulcer (DFU) present a complex pathology for clinicians to manage. This is partly attributed to the multi‐factorial nature of the disease, which may include; altered foot architecture leading to excessive plantar pressures and frictional forces peripheral arterial disease and loss of protective sensation. In addition, to the above co‐morbid variables, it is understood that a delayed wound healing state may be perpetuated by the presence of microorganisms residing in the wound tissue. The microbiology of chronic DFUs has often been reported as being polymicrobial. Of growing interest is the presence and potential role of anaerobic microorganisms in the pathology of DFUs and how they may contribute to the infective process or delayed healing. The presence of anaerobes in DFUs has been greatly underestimated, largely due to the limitations of conventional culture methods in identifying them from samples. Advancements in molecular and microscopy techniques have extended our view of the wound microbiome in addition to observing the growth and behaviour (planktonic or biofilm) of microorganisms in situ. This review paper will reflect on the evidence for the role and significance of anaerobes in DFUs and infection. A focus of this review will be to explore recent advancements in molecular genomics and microscopy techniques in order to better assess the roles of anaerobic bacteria in chronic DFUs and in biofilm‐based wound care.